Notions of justice in payments for ecosystem services: Insights from China's Sloping Land Conversion Program in Yunnan Province. (February 2015) - He, Jun; Sikor, Thomas
Highlights: China's Sloping Land Conversion Program (SLCP) is the world's largest payments for ecosystem services (PES) scheme. State policy on the SLCP contains provisions for distributive and procedural justice. Villagers, local officials and state policy share the concern about distributive justice. The shared distributive concern contributes to reforestation and rising incomes. Research needs to consider notions of justice for a fuller understanding of PES. Abstract: China's Sloping Land Conversion Program (SLCP) pays millions of farmers to convert cropland in upper watersheds to tree plantations. It is considered one of the world's largest payments for ecosystem services (PES) scheme for its reliance on financial incentives. This paper examines the outcomes of the SLCP by way of a case study from the Yangliu watershed in Yunnan province. It focuses on the notions of justice embedded in state policy and held by villagers and local state officials in order to understand the observed outcomes in terms of people's participation in the implementation of the SLCP, land use changes and livelihood effects. Villagers, local state officials, and state policy share a primary concern about distributive justice despite significant differences in their specific notions. The shared concern underlies the villagers' positive reactions to the SLCP, which among other factors, have led to the intended expansion of tree plantations and a livelihood transition in Yangliu since 2003. The insights from Yangliu suggest the need to consider justice for a fuller understanding of the dynamics and outcomes of the SLCP and other PES schemes worldwide as the notions of justice applied by the involved actors may influence land use and livelihood dynamics in addition to the other factors considered in research this far.